PERBEDAAN TEKNIK MORDANTING TERHADAP HASIL PENCELUPAN PEWARNA ALAM EKSTRAK URANG ARING (ECLIPTA ALBA (L) HASSK) DENGAN MORDAN TAWAS PADA BAHAN SUTERA - Fitriani, Fitriani; Ramainas, Ramainas; Adriani, Adriani (Journal of Home Economics and Tourism, 2013)
The purposeof this studyistorevealthe differencemordantingtechniquetocolor/Hue, darkbrightcolor/Value, andflatnessresulting coloronsilkdyeingextractsurangusingaring(Ecipta alba(L) Hassk). This type of researchis anexperimental study. VariableXisurangextractaring(Ecipta alba(L) Hassk) are dyedwithsilk material. VariableX1is anaturaldyedyeingextractsurangaring(Ecipta alba(L) Hassk) on thepremisesof silk materialispre-mordant alummordanting, theMeta-Mordanting X2, andX3arethe post-mordanting. As well asdifferences inoutcomevariableYdyes thatinclude: Ydifferences incolor/Huedyeingresults, Y2darkbrightcolordifference(Value), andY3is theflatness ofthe colordifference. Data usedin this studyisprimary data. Sources of datain this study were15respondents. Engineeringanalysis of dataprocessedandarrangedin the form ofa table, and thenanalyzed byanalysis of variance(ANOVA) one-way. Processedusing SPSS(StatisticalProductand Service, Solution) 16.0.Dariversion ofthe analysis of dataonthe value ofthe colordifference(Valueandflatnesscolor) producedfromsilkdyeingusingnatural dyesextracturangaringlight darkvalues ​​obtainedFhitung=9,556, andtothe flatness ofthe colorobtainedFcount=3.588. AndFfordarkcolortable(Value) colorandflatnesshypothesis testvalue0.514F value>FtableHoditerima, there are differences inthe results ofdyeingdarkbrightcolor(Value) due tothe effect of differentconcentrations ofaluminpre-mordanting, meta-mordanting, post-mordanting onsilkusingextractsurangaring. ForflatnessandcolorHois accepted,there are differences inthe results offlatnessdyeingcolordifferencesdue to the influenceof pre-concentration of alummordanting, meta-mordanting andpost-mordanting onsilkusingextractsurangaring. Kata kunci: Perbedaan teknik mordanting, hasil pencelupan bahan sutera ekstrak urang aring, mordan tawas